Nature Of The Diophantine Equation + = (International Journal of Innovative Research in Computer Science & Technology, 2021)
In this work, we discuss that the  Diophantine equation 4 +12 = 2has no non-negative  integer solution where x, y and z are non-negative integers.
Keywords: Exponential Diophantine Equation; Quadratic Congruence